Quantification of systemic delivery of substrates for intermediate metabolism during citrate anticoagulation of continuous renal replacement therapy - Balík, Martin; Zakharchenko, Mikhailo; Otáhal, Michal; Hrubý, Jan; Polák, Ferdinand; Rusinová, Kateřina; Stach, Zdeněk; Vávrová, Jaroslava; Jabor, Antonín (Blood purification, 2012)
BACKGROUND: There are limited data on systemic delivery of metabolic substrates during citrate anticoagulation. The direct citrate measurements are usually not available. METHODS: Patients on 2.2% acid-citrate-dextrose (ACD, n = 41) were compared to a control group on unfractionated heparin (n = 17). All were treated on 1.9-m(2) polysulfone filters. Samples were taken from the central venous catheter, ports pre- and post-filter and from effluent. RESULTS: The gain of citrate in CVVH (n = 18) was not different from CVVHDF (n = 23, p = 0.8). Mean gain of citrate was 25.4 ± 6.4 mmol/h. The systemic loads of lactate (p = 0.12) and glucose (p = 0.23) in CVVH were similar to CVVHDF. Mean inputs of lactate and glucose were 62.9 ± 21.1 and 26.6 ± 10.4 mmol/h, respectively. The mean difference between post- and prefilter unmeasured anions (d-UA) correlated with mean difference of citrate concentrations (p < 0.0001, r(2) = 0.66). The estimated caloric load of the citrate modalities was 5,536 ± 1,385 kJ/ 24 h. CONCLUSIONS: ACD might represent a significant load of metabolic substrates, particularly if used with lactate buffer. Systemic delivery of citrate can be predicted using d-UA in the extracorporeal circuit.
Keywords: akutní poškození ledvin; Acute Kidney Injury; prospektivní studie; heparin; Humans; lidé; antikoagulancia; kyselina citronová; kyselina mléčná; Equipment Design; Lactic Acid; Anticoagulants; glukosa; design vybavení; náhrada funkce ledvin; Prospective Studies; Renal Replacement Therapy; Heparin; Glucose; Citric Acid